Forma e função: uma potencialização mútua em Ensaio sobre a cegueira, de José Saramago - Castro, Paulo Henrique Passos de (2021)
At least since the 19th century, novelists have made the novel genre a space in which not only a story is told, but in which reflections and analyzes of society and human beings are developed, making the novel a space for search and investigation. José Saramago's production fits into this conception of the novel as a place of search insofar as, with his work, especially the novel, the Portuguese writer puts into practice a scrutiny of what the human being is. With this research, the objective is to analyze how José Saramago's scrutinizing fiction is constructed, with a focus on Ensaio sobre a cegueira. For this, it is observed how, in the European novel, the concept of the novel is developed as a space for reflections aimed at a broader understanding of the human being. The insertion of José Saramago's novel production in European production is then comparatively analyzed, based on what characterizes the so-called realist novel and seeing to what extent what the Portuguese author writes diverges from it. We then analyze what we decided to call José Saramago's scrutinizing fiction, so called because in it the movements of search and investigation of the self and the other prevail. The ideas of form and function, which in different perspectives were used in literary production, are then considered in the development of reflections, always taking into account the Saramago’s production. Thus, a possible conclusion reached with this research is that Ensaio sobre a cegueira is a crucial point in the work of José Saramago, as this novel, by the ways (allegorical and essay) with which it is written, seems to reach another level of search that for all his work José Saramago did not stop doing.